Quantifying Not Only Bone Loss, but Also Soft Tissue Swelling, in a Murine Inflammatory Arthritis Model Using Micro‐Computed Tomography. (February 2015) - Perilli, E.; Cantley, M.; Marino, V.; Crotti, T. N.; Smith, M. D.; Haynes, D. R.; Dharmapatni, A. A. S. S. K.
Abstract In rodent models of inflammatory arthritis, bone erosion has been non‐invasively assessed by micro‐computed tomography (micro‐CT). However, non‐invasive assessments of paw swelling (oedema) are still based on clinical grading by visual evaluation, or measurements by callipers, not always reliable for the tiny mouse paws. The aim of this work was to demonstrate a novel straightforward 3D micro‐CT analysis protocol capable of quantifying not only joint bone erosion, but also soft tissue swelling, from the same scans, in a rodent inflammatory arthritis model. Balb/c mice were divided into two groups: collagen antibody‐induced arthritis (CAIA) and CAIA treated with prednisolone, the latter reflecting an established treatment in human rheumatoid arthritis. Clinical paw scores were recorded. On day 10, front paws were assessed by micro‐CT and histology. Micro‐CT measurements included paw volume (bone and soft tissue together) and bone volume at the radiocarpal joint, and bone volume from the radiocarpal to the metacarpophalangeal joint. Micro‐CT analysis revealed significantly lower paw volume (−36%, P < 0.01) and higher bone volume (+17%, P < 0.05) in prednisolone‐treated CAIA mice compared with untreated CAIA mice. Paw volume and bone volume assessed by micro‐CT correlated significantly with clinical and histological scores (|r| > 0.5, P < 0.01). Untreated CAIA mice showed significantly higher clinical scores, higher inflammation levels histologically, cartilage and bone degradation, and pannus formation, compared with treated mice (P < 0.01). The presented novel micro‐CT analysis protocol enables 3D‐quantification of paw swelling at the micrometre level, along with the typically assessed bone erosion, using the same images/scans, without altering the scanning procedure or using contrast agents.